Pendidikan Islam Berwawasan Budaya - Suluri, Suluri (Ta'allum: Jurnal Pendidikan Islam, 2019)
Education and culture are two things that cannot be separated, education also determines the existence of a culture or the development of culture along with science which eventually becomes a civilization. Islamic education is an effort to build a culture of a society so as to create a modern, advanced, and harmonious life based on Islamic values. Islam carries the Rahmatan Lil ‘Aalamiin mission (expressing love in the universe. Thus, Islamic educational institutions with cultural insight are a mandatory mission to prove that Islam is Rahmatan lil‘ Aalamiin.